2011
DOI: 10.1111/j.1471-4159.2011.07497.x
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: The oxysterol 27‐hydroxycholesterol regulates α‐synuclein and tyrosine hydroxylase expression levels in human neuroblastoma cells through modulation of liver X receptors and estrogen receptors–relevance to Parkinson’s disease

Abstract: Loss of dopaminergic neurons and α-synuclein accumulation are the two major pathological hallmarks of Parkinson’s disease (PD). Currently, the mechanisms governing depletion of dopamine content and α-synuclein accumulation are not well understood. We showed that the oxysterol 27-hydroxycholesterol (27-OHC) reduces the expression of tyrosine hydroxylase (TH), the rate-limiting enzyme in dopamine synthesis, and increases α-synuclein levels in SH-SY5Y cells. However, the cellular mechanisms involved in 27-OHC eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 105 publications
(196 reference statements)
2
51
0
Order By: Relevance
“…In SH-SY5Y cells, 24-hydroxycholesterol and 27-hydroxycholesterol, which are ligands for LXR, have differential effects on tyrosine hydroxylase and α-synuclein: 24-hydroxycholesterol increases the levels of tyrosine hydroxylase, whereas 27-hydroxycholesterol increases the levels of α-synuclein (37). 27-Hydroxycholesterol activates LXRβ and induces its binding to LXRE in the α-synuclein promoter, up-regulating α-synuclein expression in SH-SY5Y cells (33,38). In these in vitro studies, LXRβ was expressed in neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 87%
“…In SH-SY5Y cells, 24-hydroxycholesterol and 27-hydroxycholesterol, which are ligands for LXR, have differential effects on tyrosine hydroxylase and α-synuclein: 24-hydroxycholesterol increases the levels of tyrosine hydroxylase, whereas 27-hydroxycholesterol increases the levels of α-synuclein (37). 27-Hydroxycholesterol activates LXRβ and induces its binding to LXRE in the α-synuclein promoter, up-regulating α-synuclein expression in SH-SY5Y cells (33,38). In these in vitro studies, LXRβ was expressed in neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 87%
“…Overall, we show that 27-OHC and the synthetic LXR agonist GW3965 increase the binding of LXRβ, not LXRα, to the α-synuclein promoter (Marwarha et al, 2011). This may be primarily attributed to the fact that α-synuclein is an LXRβ-regulated gene rather than LXRβ being more abundantly expressed in SH-SY5Y cells.…”
Section: Introductionmentioning
confidence: 79%
“…α-Synuclein contains two cholesterol-binding domains [3], and one study on cell culture found that α-synuclein aggregation could be induced by cholesterol and reduced by lipid-lowering medicines such as statins [4]. Moreover, the cholesterol derivative-27-hydroxycholesterol was suggested to increase the level of α-synuclein and reduces dopamine synthesis [5]. Therefore, lipids, especially cholesterol, may play a role in the pathogenesis of PD.…”
Section: Introductionmentioning
confidence: 99%